1983
DOI: 10.1542/peds.71.5.774
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Disorders of Fecal Continence in Children

Abstract: A group of 176 patients aged 2 to 15 years was investigated for idiopathic disorders of bowel function other than Hirschsprung's disease. Anorectal motility, as well as colorectal transit of radiopaque markers, were investigated. Before the end of the first month of life, 70 of the patients were constipated. Resting pressure was more unstable (P < 0.001) and higher than normal in the rectal ampulla and upper anal canal (P < 0.01). Retardation of markers occurred in the proximal and/or distal larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 0 publications
3
13
1
Order By: Relevance
“…ROM have been used since the 1980s to assess colonic transit time in both healthy children and children with GI dysmotility (20)(21)(22). Mean colonic transit times reported in studies on healthy children range from 15.1 to 39.6 hours (20,(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…ROM have been used since the 1980s to assess colonic transit time in both healthy children and children with GI dysmotility (20)(21)(22). Mean colonic transit times reported in studies on healthy children range from 15.1 to 39.6 hours (20,(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the clinical characteristics of children with constipation who had normal or prolonged colonic transit times were essentially similar, although the children with prolonged transit times had a higher frequency Thirty-seven percent of the children in our study showed delayed transit in the left colon and rectosigmoid colon. This constitutes the most commonly reported pattern in childhood constipation (6,43,44), suggesting evacuation obstruction. The results of our study support this hypothesis because up to 64% of the children with delayed transit times showed anismus when attempting to defecate.…”
Section: Discussionmentioning
confidence: 79%
“…Thirty‐seven percent of the children in our study showed delayed transit in the left colon and rectosigmoid colon. This constitutes the most commonly reported pattern in childhood constipation (6,43,44), suggesting evacuation obstruction. The results of our study support this hypothesis because up to 64% of the children with delayed transit times showed anismus when attempting to defecate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Simultaneously, careful examinations of the traces of rectoanal manometry revealed some interesting functional abnormalities, which can be classified according to their origin: smooth muscle and striated external anal sphincter (5).…”
mentioning
confidence: 99%